Modern Moldovan Theatre: A Return to the Origins - Irina E. Katereva (Publishing house "Sreda", 2020)
The article examines one of the trends in the development of modern Moldavian theatre. Being complex and multifaceted phenomenon, it is generally influenced by the direction of society's development. At the present stage its development is based on the influence of two simultaneously existing and opposing directions. One is directed outwards, expanding the range of his contacts with theaters of other countries and reflecting the principle of transculturalism. Since the 90s of the previous century, the art of actors in the Moldovan theater, the specificity of their expressiveness appeals to the experience of world's theatrical art in all its integrity, where archaic and modernity, East and West, complementing each other, serve mutual development. Another vector of development, fundamental, is directed inward. It is connected with the deep processes that affected the dramatic art of Moldova. The theatre rushed to its inner support, to the origins, from the depths of which the national theatrical tradition grows and where myth, ritual, archetype reign inseparably. At the junction of archaic and modernity, the theatre is looking for an opportunity to reveal the spiritual space of the people, the world of ancestral archetypes, the authentic unconscious. Through the art of acting to express the enduring features of the soul, the «ethnic cosmos». Research methods: theoretical analysis, generalization of scientific researches, Internet materials, systematic analysis of theatrical practice. Author concludes that modern Moldovan theatre develops under the influence of two interrelated vectors of development, existing simultaneously and oppositely directed.